Mitigating High-Fat Diet-Induced Testicular Oxidative Stress and Fibrosis with Bromelain - Gültekin, Burcu; Özen Koca, Raviye; Canbaz, Halime Tuba; Savaş, Hasan Basri; Başaran, Mustafa Berk; Solak Görmüş, Z Işık (The European Research Journal, 2026)
Objectives: Obesity induced by a high-fat diet (HFD) is closely associated with impaired male fertility, primarily through oxidative stress, inflammation, and testicular dysfunction. Natural compounds with antioxidant and anti-inflammatory properties have gained increasing attention for their potential therapeutic effects. Bromelain, a proteolytic enzyme complex derived from Ananas comosus, exhibits antioxidant, anti-inflammatory, and antifibrotic activities, suggesting potential protective effects against obesity-related reproductive impairments. Methods: Male Wistar rats were randomly assigned to four groups (n=9 per group). Animals were fed an HFD for 12 weeks to induce obesity, followed by one month of bromelain supplementation. Testicular tissues were histologically assessed using hematoxylin & eosin (H&E) and Masson’s trichrome staining. Serum and testicular samples were analyzed for antioxidant and oxidative stress markers, including paraoxonase-1 (PON1), arylesterase (ARE), total antioxidant status (TAS), total oxidant status (TOS), and oxidative stress index (OSI). Results: The HFD group showed significant testicular alterations, including thickening of the tunica albuginea, perivascular collagen accumulation, germ cell loss, and disrupted seminiferous tubule architecture (P<0.0001). Biochemically, TAS (P<0.0001) and PON1 (P=0.0041) levels were significantly decreased, whereas TOS (P<0.0001) and OSI (P<0.0001) levels were elevated. Bromelain supplementation mitigated histopathological changes, reducing collagen deposition and tunica albuginea thickness. Moreover, Bromelain significantly restored TAS and PON1 levels while decreasing TOS and OSI. No significant differences were observed in ARE (P=0.0002) activity between the groups. Conclusions: Bromelain supplementation attenuated HFD-induced oxidative stress and fibrotic alterations in testicular tissue, improving both histological and biochemical parameters. These findings suggest that Br may be a potentially beneficial natural supplement for alleviating obesity-induced impairments in male reproductive functions and associated metabolic dysfunctions.